London's Marginal Histories - Rogers, Nicholas (Labour / Le Travail, 2007)
The article reviews and comments on several books including "Violent London: 200 Years of Riots, Rebels an Revolts," by Clive Bloom, "Down and Out in 18th-Century London," by Tim Hitchcock, and "The London Mob: Violence and Disorder in 18th-Century England," by Robert Shoemaker.
Keywords: BLOOM, Clive; BOOKS -- Reviews; DOWN & out in 18th Century London (Book); HITCHCOCK, Tim; LONDON Mob: Violence & Disorder in 18th Century England, The (Book); Nonfiction; SHOEMAKER, Robert; VIOLENT London: 2000 Years of Riot, Rebels & Revolts (Book)